Answer:
[tex]\textsf{A)}\quad -2x^6+7x^4+3x^3-3x^2+11x+20[/tex]
B) Yes → Commutative Law
Step-by-step explanation:
Part (A)
To find the product of the given quadratic expressions, place each expression in brackets then multiply them:
[tex]\implies (-2x^3+x-5)(x^3-3x-4)[/tex]
Distribute the parentheses:
[tex]\implies -2x^3(x^3)-2x^3(-3x)-2x^3(-4)+x(x^3)+x(-3x)+x(-4)-5(x^3)-5(-3x)-5(-4)[/tex]
Simplify:
[tex]\implies -2x^6+6x^4+8x^3+x^4-3x^2-4x-5x^3+15x+20[/tex]
Group like terms:
[tex]\implies -2x^6+6x^4+x^4+8x^3-5x^3-3x^2-4x+15x+20[/tex]
Combine like terms:
[tex]\implies -2x^6+7x^4+3x^3-3x^2+11x+20[/tex]
Part (B)
According the to Commutative Law (for multiplication) changing the order or position of two numbers does not change the end result.
[tex]\textsf{Commutative Law}: \quad a \cdot b = b \cdot a[/tex]
Therefore:
[tex](-2x^3+x-5)(x^3-3x-4)=(x^3-3x-4)(-2x^3+x-5)[/tex]